Kajian Kesesuaian Wisata Bahari di Perairan Labuhan Amuk, Karangasem, Bali - Ardianto, Muhammad Rizal; Perwira, Ima Yudha; Darmendra, I Putu Yogi (Bumi Lestari; Vol 24 No 2 (2024), 2024)
This research examines the potential for marine tourism at Labuhan Amuk Beach, located in Antiga Village, Manggis Sub-district, Karangasem District. The beach is conducive to marine tourism activities, although there is a dearth of comprehensive research on its environmental characteristics. However, certain limiting factors were identified, such as the type of beach and land cover at specific stations. These factors may be influenced by various elements, including the proximity to tributaries carrying sediments and rocks from Mount Agung, as well as the presence of buildings near the beach to support tourist activities. The study emphasized the importance of analyzing the suitability of marine tourism locations to ensure the safety and security of tourists and marine tourism businesses. The data collection process, using a descriptive method and random sampling, took place at six points between September and November 2023 and involved parameters such as water depth, coastal type, beach width, water base material, water flow, beach slope, water brightness, land closure, harmful biota, and freshwater availability. The findings of this study have influenced the formulation of a development strategy for conducting coral reef transplantation efforts. This strategy involves external management and the resumption of tourist attractions halted due to the COVID-19 pandemic.